Pengaruh Celebrity Endorser, Electronic Word of Mouth, Content Marketing Tiktok terhadap Keputusan Pembelian Produk Scarlett Whitening - Calista Rizqy Maudy; Christina Yanita Setyawati (Jurnal Syntax Admiration, 2024)
Scarlett Whitening is a company engaged in the beauty sector and has been officially established since 2017. The Scarlett Whitening company uses social media as a tool to market products and find out customer needs and wants. The aim of this research is to understand the influence of celebrity endorser, electronic word of mouth, content marketing TikTok towards purchase decision of Scarlett Whitening product. This research uses quantitative descriptive alongside with purposive sampling. This research the sample used was 97 people with an age range of 16-60 years. The researchers use SPSS version 26 to process the data, with multiple linear regression as the main method. Based on the result of the study, it is indicated that the electronic word of mouth and content marketing does not significantly influence Purchase decision, while the celebrity endorser has a significant effect on purchase decision of Scarlett Whitening product.Celebrity endorsers, electronic word of mouth and content marketing together can measure the dependent variable, namely purchasing decisions.